The Comparison on Mold Design for Injected Molded Integral Hinges Test Sample Via Autodesk MoldFlow Adviser 2019 - Mohd Hilmi Othman,; M. Nidzuwan, (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Plastic injection molding has been in high demand today. In this study, the Moldflow Adviser is used to make the comparison on mold design for injected molded integral hinges test sample. The injection molding machine and product used in this research are Nissei NP7F and integral hinges test sample that available in UTHM lab. Computer models or simulation in injection molding can be categorized into three groups, such as, modeling, optimization and process control. The designs that are used of injection molding are divided into six design which involves change of feeding system parameter. On this study, processing conditions selected were filling time, filled temperature, weld lines, warpage, air traps, volumetric shrinkage and product quality. Before start the mold design process condition in simulation software, integral hinges test sample has been drawn in SolidWorks software first then transfer to Moldflow Adviser software in STL file format. For this study, feeding system has been change for every design. In order to obtain the data of product, the evaluation of criteria analysis have been made. As the result, comparison of product quality analyzed. In a conclusion, the result of comparison indicated that Design 6 have the high product quality with the uniform filled temperature 222.7℃, lowest volumetric shrinkage 12.14%, and 48 air traps only. However, Design 2 has advantage on lowest warpage values and Design 3 are good in filling time and lowest weld lines values compared to Design 6